An Effort of Chemistry Graduate Students Publishing an Article in Scopus-indexed Journals - Lastika Ari Prihandoko; Joko Nurkamto; Sri Marmanto (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The global competition between universities encourages an increase in the number of article publications in various international journal publishers. The demand to have article publication is unequal with the ability of academic writing skill, primarily by graduate students who are mostly novice writers. This study aims to determine the efforts of postgraduate students to publish their articles in reputable international scientific journals in the framework of the process of academic writing. This study used questionnaires and interviews as a method to obtain data from postgraduates majoring in chemistry who have Scopus indexed publications. The chemistry students have difficulties in finding a topic, organizing paragraphs, revising the article, and proofreading. This study expected to be a reference for academics who want to have Scopus-indexed publications and can be developed into teaching materials to provide practical steps for students in writing.